FAKTOR – FAKTOR KARAKTRISTIK RESPONDEN YANG MEMPENGARUHI RESPONTIME WAKTU TUNGGU PASIEN RAWAT JALAN DI PUSKESMAS GEMPOL - Hanna Sukmawati; Titis Eka Gusti; Eka Yumanisari (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2022)
The quality of health services is a health service that can satisfy every service user of health services in accordance with the level of satisfaction of the average population and its implementation is in accordance with professional standards and codes of ethics. , friendliness and comfort of service. Respontime patient waiting time has an impact on patient satisfaction. A service is said to be good by the patient is determined by the fact that the services provided can meet the patient's needs by using the patient's perception of the service received. The purpose of this study was to describe the response time of waiting time at the Gempol Public Health Center. This study uses descriptive research with a quantitative approach. The population in this study was the average number of outpatients in 3 months, from November to January 2022, the sample in this study was 58 outpatients. The results showed that the respondent's characteristic factor to the response time of waiting time at the Gempol Public Health Center was 58 respondents, 49 respondents said that the waiting time was > 10 minutes (not appropriate) and 9 people said that it was < 10 minutes (appropriate). Based on the results of this study, it is expected that officers can register according to the SOP, which is < 10 minutes so that patients do not wait long for registration.